2002
DOI: 10.4049/jimmunol.169.3.1326
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Class II MHC Expression in APCs: Roles of Types I, III, and IV Class II Transactivator

Abstract: Class II transactivator (CIITA) is necessary for expression of class II MHC (MHC-II) molecules. In mice, CIITA expression is regulated by three promoters (pI, pIII, and pIV), producing types I, III, and IV CIITA. The relative roles of different CIITA types remain unclear. Unstimulated bone marrow-derived macrophages expressed low levels of CIITA mRNA; type I CIITA was nine times more abundant than type IV (type III CIITA was barely detected). Exposure to IFN-γ (6 h) dramatically increased types I and IV CIITA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
99
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(112 citation statements)
references
References 44 publications
12
99
1
Order By: Relevance
“…The putative regulatory region acts as a STAT-1-dependent and IRF-1-independent enhancer [43]. In contrast to these findings in human cells, pIII does not seem to be inducible by IFN-+ in primary rat astrocytes [48] or in mouse macrophages [40,49]. Moreover, pIII is not sufficient for driving IFN-+ -induced CIITA and MHCII expression in non-BM-derived cells of the pIV knockout mice [40].…”
Section: Ifn-q -Stimulated Cellsmentioning
confidence: 68%
“…The putative regulatory region acts as a STAT-1-dependent and IRF-1-independent enhancer [43]. In contrast to these findings in human cells, pIII does not seem to be inducible by IFN-+ in primary rat astrocytes [48] or in mouse macrophages [40,49]. Moreover, pIII is not sufficient for driving IFN-+ -induced CIITA and MHCII expression in non-BM-derived cells of the pIV knockout mice [40].…”
Section: Ifn-q -Stimulated Cellsmentioning
confidence: 68%
“…Previous studies in primary human monocytes are limited to a single observation that type III CIITA is expressed in freshly isolated cells, albeit at low levels (37). Using primary cells, a recent study found that murine bone marrow-derived macrophages (derived in the presence of M-CSF) and thioglycolate-elicited peritoneal macrophages express low levels of type I CIITA, with types I and IV CIITA induced in IFN-␥-activated cells (38). In addition, macrophages from CIITA PIV knockout mice express CIITA driven from PI following IFN-␥ treatment (34).…”
Section: Discussionmentioning
confidence: 99%
“…DC have been reported to express all three isoforms of CIITA: type I (expressed only in cells of the monocyte lineage and containing a unique N-terminal caspase recruitment domain), type III (also expressed in B cells), and type IV (whose expression is induced by IFN-␥) (13,(15)(16)(17). Type I and type III CIITA comprise most of the CIITA expressed by immature DC, but maturation induces a precipitous decline in levels of type I and type III CIITA mRNA and protein (16,18). This decrease correlates with the shutdown of MHC class II transcription and the shift from Ag processing to Ag presentation (16).…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%